KETERAMPILAN BERBICARA SISWA KELAS VA SD NEGRI 48 PEKANBARU - Khafifah Khairani; Febrina Dafit (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to determine the speaking skills and describe the speaking skills of class Va students at SDN 48 Pekanbaru. The approach method used in this research is qualitative. In carrying out the research, researchers used qualitative descriptive data analysis techniques. Data collection was carried out using test, interview and observation data. The data taken and collected comes from class teachers and class VA students. Data analysis was carried out through three implementation stages, namely data reduction, data presentation and drawing conclusions. Checking the validity of the data used includes extending the time of researcher involvement in the research process, increasing persistence, triangulation and analysis of negative cases. The research results obtained showed that the speaking skills of class VA students at SDN 48 Pekanbaru were in the good category. The student's speaking skills include aspects of vocal accuracy, aspects of voice intonation, aspects of speech accuracy, aspects of acquisition fluency. Factors that influence students' speaking skills include supporting factors and inhibiting factors. Supporting factors are self-confidence, home environment and students' daily interactions with their peers. Meanwhile, inhibiting factors are the student's individual attitudes, study habits and the student's living environment.